Cutting behaviour of porcelain stoneware slabs: A microstructural evaluation. Issue 19 (1st October 2022) - Rambaldi, E.; La Torre, V.M.; Tartaglia, A.
Abstract: The study concerns the characterisation of five porcelain stoneware slabs with thicknesses of 12 and 20 mm and different cutting responses. Two slabs showed a deviation from a linear cut, resulting in a poor response to the diamond disk, while the other three slabs reacted well. In order to highlight any differences between these slabs, mineralogical and microstructural analyses were carried out, including the determination of a sintering index, total porosity and pore size distribution. This approach is based on a "reverse engineering" concept whereby the cause of the cutting effect can be traced by analysing the finished product. Both the total porosity values and the sintering index can be considered as critical parameters to evaluate the cutting responses of ceramic slabs. The best compromise to obtain a good cutting response, in porcelain stoneware slabs, is reached when the total porosity is the maximum possible, pores are the smaller as possible and the sintering index is the minimum possible, without compromising the quality and technical performance of the porcelain stoneware.